2020
DOI: 10.1101/2020.05.27.118331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of microbiome variation among infrapopulations of permanent bloodsucking parasites

Abstract: While interspecific variation in microbiome composition can often be readily explained by factors such as host species identity, there is still limited knowledge of how microbiomes vary at scales lower than the species level (e.g., between individuals or populations). Here, we evaluated variation in microbiome composition of individual parasites among infrapopulations (i.e., populations of parasites of the same species living on a single host individual). To address this question, we used genome-resolved and s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Indeed, our phylogenomic trees, between‐individual kinship coefficients, and estimates of among‐infrapopulation F ST 's consistently showed that lice collected from the same Saimaa ringed seal individual are on average genetically more similar than are individuals collected at random from the host population. Notably, the population‐genetic differentiation found across lice collected from different seal individuals is not the only aspect that is affected by the fact that seal lice are distributed into distinct infrapopulations: Using the same specimens that were analysed in this study, Doña et al (2021) found that infrapopulation identity explained a major proportion of the variation in microbiome composition within individual lice.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, our phylogenomic trees, between‐individual kinship coefficients, and estimates of among‐infrapopulation F ST 's consistently showed that lice collected from the same Saimaa ringed seal individual are on average genetically more similar than are individuals collected at random from the host population. Notably, the population‐genetic differentiation found across lice collected from different seal individuals is not the only aspect that is affected by the fact that seal lice are distributed into distinct infrapopulations: Using the same specimens that were analysed in this study, Doña et al (2021) found that infrapopulation identity explained a major proportion of the variation in microbiome composition within individual lice.…”
Section: Discussionmentioning
confidence: 76%